Male and Female Student’s Linguistic Politeness in Speaking Classroom - Oktanika Wahyu Nurjanah; Riyadi Santosa; Dewi Rochsantiningsih (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
Communicative competence emphasizes that the knowledge of grammatical rules is not sufficient to communicate comprehensively, therefore it needs pragmatic knowledge. Without pragmatic understanding, there will be many failures in communication for example is misunderstanding. Besides, one important aspect of pragmatic competence is politeness. Many researches have been conducted in this field, however only few that specifically revealed the differences between male and female linguistic politeness in speaking classroom, whereas its primary data are utterances. It becomes a consideration of this research to be conducted in the speaking classroom of university student, especially international relations major students. The observation is conducted based on the adaptation from DCT by Bacha, Bahous & Diab (2012). Furthermore, the data are analyzed using some politeness theories. The result showed that in general, female students are more polite compared to male students. At last, teachers should understand this fact by do not expecting male students to be as polite as female, basically they are unique their way..